Arte, tempo, fim do mundo e salvação (a partir da filosofia) - Miguens, Sofia (2022)
In this article I consider the problem of how art and time relate starting from a currently widely accepted anti-essentialist definition of art, Jerry Levinson's intentionalhistorical definition. According to such definition, art is what is intentionally proposed as art by an artist against the background of the history of art, independently of the intrinsic properties of objects. The problem, though, is what we mean by 'history' here. In order to highlight some of the assumptions of such approach (namely where these concern language) I explore the background of Walter Benjamin's idea that art is the sole salvation and revolution possible. I do it by appealing to Israeli philosopher Eli Friedlander's interpretation of Benjamin's work.